2016
DOI: 10.1155/2016/9259646
|View full text |Cite
|
Sign up to set email alerts
|

Biologics for Targeting Inflammatory Cytokines, Clinical Uses, and Limitations

Abstract: Proinflammatory cytokines are potent mediators of numerous biological processes and are tightly regulated in the body. Chronic uncontrolled levels of such cytokines can initiate and derive many pathologies, including incidences of autoimmunity and cancer. Therefore, therapies that regulate the activity of inflammatory cytokines, either by supplementation of anti-inflammatory recombinant cytokines or by neutralizing them by using blocking antibodies, have been extensively used over the past decades. Over the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(118 citation statements)
references
References 154 publications
(123 reference statements)
2
116
0
Order By: Relevance
“…IL-6 is a known inflammatory cytokine that has an effect on a variety of cells in the immune system, including macrophages 25 . A previous study has shown that along with other inflammatory markers, IL-6 is elevated in patients with bacterial pneumonia 26 .…”
Section: Resultsmentioning
confidence: 99%
“…IL-6 is a known inflammatory cytokine that has an effect on a variety of cells in the immune system, including macrophages 25 . A previous study has shown that along with other inflammatory markers, IL-6 is elevated in patients with bacterial pneumonia 26 .…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports on the targeting of these enzymes for potential therapeutic applications [21]. In this study, drug targets for these proteins were identified and virtual screening was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…High Bcl‐2 expression is closely related to oestrogen production and estrogen receptor expression (Andrew et al., ). However, Bcl‐2 expression may be influenced by other factors, such as local or systemic cytokines (Rider, Carmi, & Cohen, ). In present study, quercetin significantly down‐regulated the expression of Bax mRNA and up‐regulated the expression of Bcl‐2 mRNA.…”
Section: Discussionmentioning
confidence: 99%